Energy-Efficient Improper Signaling for $K$-User Interference Channels - Soleymani, Mohammad; Lameiro, Christian; Santamaria, Ignacio; Schreier, Peter J. (Proc. IEEE European Signal Processing Conference (EUSIPCO))

Improper Gaussian Signaling for the Two-user Broadcast Channel Treating Interference as Noise - Lameiro, Christian; Santamaria, Ignacio; Schreier, Peter J (ICASSP 2019-2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Improper Gaussian Signaling for Multiple-Access Channels in Underlay Cognitive Radio - Lameiro, C.; Santamaría, I.; Schreier, P. J. (IEEE Transactions on Communications)

Two-channel passive detection exploiting cyclostationarity - Horstmann, Stefanie; Ramírez, David; Schreier, Peter J. (Proc. 27th European Signal Proc. Conf. (EUSIPCO))

Two-channel passive detection of cyclostationary signals in noise with spatio-temporal structure - Horstmann, Stefanie; Ramírez, David; Schreier, Peter J.; Pries, Aaron (Proc.\ Asilomar Conf.\ Signals\ Syst. Computers)

Benefits of Improper Signaling for Overlay Cognitive Radio - Lameiro, Christian; Santamaría, Ignacio; Schreier, Peter J (Proc. Globecom)

A von Hamos-type hard X-ray spectrometer at the PETRA III beamline P64 - Kalinko, Aleksandr; Caliebe, Wolfgang A.; Schoch, Roland; Bauer, Matthias (Journal of Synchrotron Radiation)
The design and performance of the high-resolution wavelength-dispersive multi-crystal von Hamos-type spectrometer at PETRA III beamline P64 are described. Extended analyzer crystal collection available at the beamline allows coverage of a broad energy range from 5 keV to 20 keV with an energy resolution of 0.35–1 eV. Particular attention was paid to enabling two-color measurements by a combination of two types of analyzer crystals and two two-dimensional detectors. The performance of the spectrometer is demonstrated by elastic-line and emission-line measurements on various compounds.
Keywords: Instrumentation; Nuclear and High Energy Physics; Radiation

Gold(ii) in redox-switchable gold(i) catalysis - Veit, Philipp; Volkert, Carla; Förster, Christoph; Ksenofontov, Vadim; Schlicher, Steffen; Bauer, Matthias; Heinze, Katja (Chemical Communications)
Gold(ii) species catalyse the cyclisation of N(2-propyn-1-yl)benzamide to 2-phenyl-5-vinylidene-2-oxazoline without halide abstraction while the neutral gold(i) complex is inactive indicating a gold(ii/i) redox-switch.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Development of trainee teachers’ analytical competence in their induction phase – A longitudinal study comparing science and non-science teachers. - Plöger, Wilfried; Scholl, Daniel; Schüle, Christoph; Seifert, Andreas (Teaching and Teacher Education)

Informal Workplace Learning: Development and validation of a measure. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (Human Resource Development Quarterly)

Improving Co-Channel Interference Robustness In Direct Detection Receivers Using A Surface Acoustic Wave (SAW) Correlator - Abughannam, Saed; Fard, Saeed; Scheytt, Christoph (Asia-Pacific Microwave Conference (APMC))
Using direct-detection architecture in Radio Frequency (RF) receivers allows for ultra-low power dissipation and is often used in Wake-Up receivers. Unfortunately direct-detection receivers suffer from high sensitivity to co-channel interference which reduces the communication performance and reliability. In this paper, it is shown that co-channel interference robustness of direct-detection receivers is improved by using Binary Phase Shift Keying (BPSK) Barker code modulated Surface Acoustic Wave (SAW) correlator as a prior stage to the RF envelope detector. Replacing the band select filter with SAW correlator does not result in higher receiver hardware cost. In our receiver, the SAW correlator functions as a passive signal processor, providing gain for a BPSK Barker code modulated signal, while suppressing in-band interferers. This improves the co-channel interference robustness of the direct-detection receiver while preserving its advantage of power efficiency. The concept is verified by means of a direct-detection receiver with discrete components on an RF PCB including an SAW Barker Code correlator at a center frequency of 2.44 GHz fabricated on Lithium Niobate substrate. Measurements with WiFi signals demonstrate that the interference robustness is improved by more than 10 dB compared to a conventional direct-detection receiver.

The Role of Saliency in Learning First Words - Wildt, Eugenia; Rohlfing, Katharina; Scharlau, Ingrid (Frontiers in Psychology)

Sprachstrukturelle Modelle. Konvergenzen theoretischer und empirischer Forschung

Sprachstrukturelle Modelle. Linguistische, spracherwerbsorientierte und didaktische Zugänge - Tophinke, Doris; Topalovic, Elvira; Rohlfing, Katharina J. (Mitteilungen des Deutschen Germanistenverbandes)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Raising Robotic Natives?: Persuasive Potentials of Social Robots in Early Education - Siebert, Scarlet; Tolksdorf, Nils Frederik; Rohlfing, Katharina J.; Zorn, Isabel (The Journal of Communication and Media Studies)

Do shy children behave differently than non-shy children in a child-robot interaction? An analysis of positive and negative expressions of shyness in kindergarten children - Tolksdorf, Nils Frederik; Dirk, Hönemann; Rohlfing, Katharina J.; Viertel, Franziska E.

When learning words with robots, children’s answers are multimodal: a challenge for a dialogue design - Tolksdorf, Nils Frederik; Mertens, Ulrich J.; Rohlfing, Katharina J.

Multimodale Kommunikation in frühen Buchlesesituationen und ihr Zusammenhang mit dem späteren Wortschatz. - Grimminger, Angela; Rohlfing, Katharina (Sprache · Stimme · Gehör)

Decontextualized talk in caregivers’ input to 12-month-old children during structured interaction. - Grimminger, Angela; Rohlfing, Katharina; Lüke, Carina; Liszkowski, Ulf; Ritterfeld, Ute (Journal of Child Language)

Utilizing Pragmatic Frames as an analytical tool for children’s performance during word learning. - Rohlfing, Katharina; Grimminger, Angela (Proceedings of the 9th Joint IEEE International Conference on Development and Learning and on Epigenetic Robotics)